18β‐glycyrrhetinic acid inhibits hepatocellular carcinoma development by reversing hepatic stellate cell‐mediated immunosuppression in mice. Issue 8 (20th October 2012) - Kuang, Penghao; Zhao, Wenxiu; Su, Weixue; Zhang, Zhengqi; Zhang, Lei; Liu, Jianming; Ren, Guangli; Yin, Zhenyu; Wang, Xiaomin
Abstract: Hepatic stellate cells (HSCs) have immunosuppressive capabilities and contribute to the occurrence and development of hepatocellular carcinoma (HCC). Thus, activated HSCs may be a suitable target for HCC therapy. Our study used mixed leukocyte reactions (MLR) in vitro to demonstrate that 18β‐glycyrrhetinic acid (GA) could reverse HSC‐mediated immunosuppression by reducing T‐cell apoptosis and regulatory T (Treg) cells expression, thereby enhancing the ability of T cells to attack tumor cells and attenuating HCC cell invasiveness. Moreover, we established a HCC orthotopic implantation model in immunocompetent C57BL/6 mice, which suggested that GA played a protective role in HCC development by reducing immunosuppression mediated by HSCs in the tumor microenvironment. Abstract : What's new? Activated hepatic stellate cells (HSCs) are potential therapeutic targets for hepatocellular carcinoma (HCC), based on their role in immunosuppression and tumor progression in mouse models. Here, the compound 18β‐glycyrrhetinic acid (GA) was investigated for possible inhibitory effects on HSCs. The compound was found to reduce HSC‐mediated immunosuppression in HCC tumor microenvironment in mice. The findings indicate that GA may be a useful adjunct for immune‐based HCC therapy.